Analysis of variations in the bronchovascular pattern of the lingular segment to explore the correlations between the lingular segment artery and left superior division veins - Li, Zhikai; Wu, Wenbo; Kong, Yuhong; Chen, Shuangqing; Zhang, Xiaopeng (Frontiers in Surgery, 2023)
Background: With the development of anatomical segmentectomy, the thoracic surgeons must master the anatomical variations of the pulmonary bronchi and vessels. However, there are only a few reports showing anatomic variations of the lingular segment (LS) using three-dimensional computed tomography angiography and bronchography (3D-CTBA). Thus, the present study aimed to analyze the bronchovascular patterns of the LS and explore the correlation between the lingular segment artery (LSA) and left superior division veins (LSDV). Materials and Methods: The 3D-CTBA data of the left upper lobe were collected from patients who had undergone lobectomy or segmentectomy at Hebei General Hospital between October 2020 and October 2022. We reviewed the clinical characteristics and variations in bronchi and pulmonary vessels and grouped them according to different classifications. Results: Among all 540 cases of 3D-CTBA, the branching patterns of LSA included 369 (68.3%) cases with the interlobar origin, 126 (23.3%) cases with the interlobar and mediastinal origin, and 45 (8.3%) cases with the mediastinal origin. The branching pattern of LSDV could be classified into three forms: Semi-central vein type (345/540, 63.9%), Non-central vein type (76/540, 14.1%), and Central vein type (119/540, 22.0%). There were 51 cases (9.4%) with Non-central vein type, 50 cases (9.3%) with Central vein type, 268 cases (49.6%) with Semi-central vein type in the interlobar type, and 7 cases (1.3%) with Non-central vein type, 9 cases (1.7%) with Central vein type, 29 cases (5.4%) with Semi-central vein type in the mediastinal type. Moreover, the Non-central vein type, the Central vein type, and the Semi-central vein type accounted for 18 (3.3%), 60 (11.1%), and 48 (8.9%) in the interlobar and mediastinal type. Combinations of the branching patterns of theLSA and LSDV were significantly dependent (p < 0.005). The combinations of the interlobar and mediastinal type with the Central vein type, and the interlobar type and mediastinal type with the Semi-central vein type were frequently observed. Conclusions: This study found the relationship between the LSA and LSDV and clarified the bifurcation patterns of the bronchovascular in the LS. Our data can be used by thoracic surgeons to perform safe and precise LS segmentectomy.